Combination Effects of Docetaxel and Doxorubicin in Hormone-Refractory Prostate Cancer Cells - Eleftheria Tsakalozou; Allison M. Eckman; Younsoo Bae (Biochemistry Research International)
Combination effects of docetaxel (DOC) and doxorubicin (DOX) were investigated in prostate cancer cells (PC3 and DU145). Combination indices (CIs) were determined using the unified theory in various concentrations and mixing ratios (synergy: CI<0.9, additivity: 0.9<CI<1.1, and antagonism: CI>1.1). DOC showed a biphasic cytotoxicity pattern with the half maximal inhibitory concentration (IC50) at the picomolar range for PC3 (0.598 nM) and DU145 (0.469 nM), following 72 h drug exposure. The IC50s of DOX were 908 nM and 343 nM for PC3 and DU145, respectively. Strong synergy was seen when PC3 was treated with DOC at concentrations lower than its IC50 values (0.125~0.5 nM) plus DOX (2~8 times IC50). Equipotent drug combination treatments (7×7) revealed that the DOC/DOX combination leads to high synergy and effective cell death only in a narrow concentration range in DU145. This study provides a convenient method to predict multiple drug combination effects by the estimated CI values as well as cell viability data. The proposed DOC/DOX mixing ratios can be used to design combination drug cocktails or delivery systems to improve chemotherapy for cancer patients.